2011
DOI: 10.4028/www.scientific.net/amr.284-286.1001
|View full text |Cite
|
Sign up to set email alerts
|

Research on Tribological Properties of Serpentine Particles as Lubricating Oil Additives

Abstract: This paper adopts wet method to prepare serpentine particles on the planetary ball mill, executes lipophilic degree tests and friction and wear tests of these particles. The results showed that: 1) as the modification agent, the optimum dosage of oleic acid is when the volume ratio of oleic acid and serpentine particles is 2, and the optimum time of milling (modification) is 24h. 2) 4012 maritime lubricating oil with serpentine particles has obvious anti-wear and friction effect, and the optimum dosage range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Nan et al [7] also used 0.5 wt% as an optimum concentration of ultrafine magnesium aluminum silicate powders, as lubricant additive in SRV oscillating friction and wear tester and found that ultrafine powder was very efficient in reducing friction and wear at different loads (10 N-100 N). Tribological characteristics of serpentine powder used in engine oil or base oil with respect to formation of tribofilm, surface modifying capabilities, reduction of friction coefficient, and wear was extensively studied by many other researchers [8][9][10][11][12][13]. Similar results on reduction of friction coefficients by 24.63% and diameters of friction spots by 41.88% as compared to the base oil were reported by Zhao et al [14].…”
Section: Introductionmentioning
confidence: 52%
“…Nan et al [7] also used 0.5 wt% as an optimum concentration of ultrafine magnesium aluminum silicate powders, as lubricant additive in SRV oscillating friction and wear tester and found that ultrafine powder was very efficient in reducing friction and wear at different loads (10 N-100 N). Tribological characteristics of serpentine powder used in engine oil or base oil with respect to formation of tribofilm, surface modifying capabilities, reduction of friction coefficient, and wear was extensively studied by many other researchers [8][9][10][11][12][13]. Similar results on reduction of friction coefficients by 24.63% and diameters of friction spots by 41.88% as compared to the base oil were reported by Zhao et al [14].…”
Section: Introductionmentioning
confidence: 52%
“…For example, the composite powders containing AMNP and nano-metal compounds such as Mo, La, Cu and Ce, have a lower friction coefficient and wear volume than that of AMNP alone. It is believed that the addition of nano metal compounds is conducive to the formation of tribofilm through ion exchange, while rare earth elements (La and Ce) mainly act catalysts [19,54,55,64,66]. The AMNP (0.1%) + Zinc dialkyl dithiophosphate (ZDDP, 1.0%) has a lower wear volume of friction pair than that of AMNP alone (Figure 7).…”
Section: Tribological Performances Of Antigoritementioning
confidence: 99%
“…The evaluation of the application effect mainly focused on the cylinder burst pressure of engine, fuel consumption of the engine, temperature of lubrication oil, CO and CH emissions of the engine, power consumption of the driving motor, vibration amplitude of gears, engine consumption of lubricating oils (Table 1, No.110 to 113). The major conclusion is that adding AMNP to traditional lubricating medium could improve cylinder pressure (increased by 2.7-11%) [85,86], reduce the consumption of engine fuel (by 2.5-7%), reduce consumption of lubricating oil (by 14.3-94.5%) [58,59,86,87], reduce the temperature of lubricating oil (9.7%) (Figure 8) [4] and reduce the emission of CO (39.5%) and CH compounds (29.5%) [86], as well as reduce power consumption of driving motor (9.12-13%) (Figure 9) [4,54,59]. Of importance is also that lubricating medium containing AMNP could obviously prolong the service life of the friction parts of the equipment and improve the service efficiency [83,87,92,93].…”
Section: Application Of Antigorite Lubricating Additivementioning
confidence: 99%
See 1 more Smart Citation
“…It has great potential as a lubricating additive due to its layered structure. And many researchers have tried to use it as a lubricating additive and get success [11][12][13][14]. But its development is restricted by its micro-size and impurities-containing.…”
Section: Introductionmentioning
confidence: 99%